Kepastian Hukum Kewenangan Pemusnahan Barang Bukti Tindak Pidana Penyalahgunaan Narkotika - N, Suhaimi.; Erwinsyahbana; Guntur Ambey (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
The destruction of evidence in narcotics abuse crimes is a crucial stage in law enforcement, as it eliminates the object of the crime while ensuring legal certainty and preventing irregularities. However, in practice, various issues remain that raise academic concerns, particularly related to procedural irregularities, weak coordination among law enforcement officials, and a lack of transparency in the evidence destruction process. This study aims to examine the mechanisms and implementation of narcotics evidence destruction based on positive legal provisions and to analyze the extent to which law enforcement officials apply the principle of legal certainty. This study uses an empirical juridical approach through an analysis of laws and regulations governing the destruction of narcotics evidence, and is supported by field data through interviews and case studies at relevant law enforcement agencies. The results show that although regulations clearly outline the destruction mechanism, its implementation remains inconsistent. Procedural differences between regions, delays in implementation, a lack of accountability documentation, and weak coordination between the police, prosecutors, and related institutions were found. Technical facility constraints also hamper the oversight and effectiveness of the destruction process. This study concludes that there is a need for technical and administrative improvements, increased integrity, and transparency of law enforcement officers so that the process of destroying narcotics evidence runs according to the principle of legal certainty.